Analisis Kinerja Manajemen Keuangan Koperasi dalam Mengoptimalkan Sisa Hasil Usaha (Studi Kasus Koperasi Dharma Nirmala Mandiri Tahun 2020–2024) - I Gede Kahar Suputra (J-Coop : Journal of Co-operative, 2026)
Despite continuous asset growth, many cooperatives experience stagnation in Sisa Hasil Usaha (SHU), indicating inefficiencies in financial management. This study aims to analyze the performance of cooperative financial management in optimizing SHU by examining profitability and operational efficiency at Koperasi Dharma Nirmala Mandiri during the 2020–2024 period. The research employs a descriptive quantitative approach using secondary data from financial statements, analyzed through profitability ratios (Return on Assets and Net Profit Margin), operational efficiency ratios, and trend analysis. The results show that total assets increased by approximately 18% over the study period, while SHU remained relatively stagnant at around Rp60 million per year. Profitability indicators reveal consistently low performance, with Return on Assets declining from 0.31% to 0.26% and Net Profit Margin decreasing from 0.88% to 0.74%. In addition, operational efficiency was weak, as operating costs absorbed nearly 98% of total operating revenues. The study concludes that the cooperative’s financial management performance has not been optimal in converting asset growth into sustainable SHU and recommends strengthening operational efficiency, improving asset productivity, and enhancing financial control to support long-term cooperative sustainability.